A strategy to identify sources of quantitative resistance in pathosystems involving disease escape and physiological resistance: the case study of rice sheath blight - Srinivasachary, S.; Beligan, G.; Willocquet, L.; Savary, S. (Wiley, 2013)
An epidemiology‐based strategy using rice sheath blight (ShB) as a biological model was developed that enables identification of sources of resistance. A set of 163 cultivated rice genotypes, including genotypes which had been reported to express partial resistance to ShB, and a few genotypes reported as very susceptible, were assessed using two complementary methods. First, microfield experiments allowed measurement of disease intensification at, and spread from, inoculated sources, along with morphological traits of each genotype. Secondly, detached tiller tests allowed measurement of the physiological resistance to the disease under conditions where morphology does not come into play. Multivariate analysis involving hierarchical cluster analysis, followed by multiple correspondence analysis, indicated that levels of physiological resistance, groups of plant morphology and disease levels in microfields were associated. Results from logistic regressions further indicated that a decreased number of lesions measured on detached tillers increased the odds of a rice genotype belonging to the group with low disease intensity in microfields. The combined results from microfield and detached tiller tests allowed identification of 23 genotypes with low level of disease intensity, which may be used as sources of resistance to ShB in breeding programmes. The results suggest that this strategy, which combines the crop stand and the individual tiller scales, may be applied to the identification of sources of resistance to a range of diseases with similar life cycle traits.